Effects of nonionic surfactants on soil structure, soil properties and soil water flow - SHENG Feng; LI Zhongrun; ZHANG Bin (Guan'gai paishui xuebao)
【Objective】Nonionic surfactants are soil amendments that could modify water surface tension, alter soil repellency, and affect water flow and distribution in soil. We experimentally investigate the effects of nonionic surfactants in reclaimed water on soil structure, soil properties and soil water infiltration, aiming to improve the management of agricultural use of reclaimed water and protect soil and water environments.【Method】Laboratory experiments were conducted using repacked soil columns to examine the influence of nonionic surfactants on soil physical properties and water infiltration. Treatments included irrigation water with 0, 0.02, 0.05, and 0.1 critical micelle concentration (CMC) of nonionic surfactants, combined with three irrigation frequencies (daily, every two days, and every three days) and an irrigation schedule alternatingly using nonionic surfactant-laden water and freshwater. Measurements in the experiment included soil aggregate stability, bulk density, capillary and non-capillary porosity, non-capillary porosity ratio, soil water repellency, surface infiltrability, and preferential flow heterogeneity.【Result】Nonionic surfactants improved soil aggregate stability and porosity but increased soil hydrophobicity and water flow instability. Low-frequency and high-amount irrigation led to disintegration of soil aggregates, while high-frequency and low-amount irrigation exacerbated preferential flow heterogeneity in water infiltration. Alternating nonionic surfactant-laden water and freshwater in irrigation enhanced soil aggregate stability, increased soil porosity, and reduced soil hydrophobicity and preferential flow.【Conclusion】Alternating irrigation with reclaimed water and freshwater can effectively balances the positive and negative effects of nonionic surfactants on soil properties and soil water infiltration. This can optimize the use of reclaimed water for agriculture while maintaining soil health and reducing environmental risks.